2019
DOI: 10.1186/s40814-019-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural therapy for the management of inflammatory bowel disease-fatigue: a feasibility randomised controlled trial

Abstract: BackgroundFatigue is the third most prevalent symptom for patients with inflammatory bowel disease (IBD), yet optimal strategies for its management are unclear. Treatment protocols for fatigue in other conditions have been based on cognitive-behavioural models. Targeting cognitions, emotions and behaviour related to fatigue through cognitive-behavioural therapy (CBT) may be a viable option to improve fatigue and quality of life (QoL) in IBD.MethodsThis single centre, two-arm, feasibility randomised controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 110 publications
(129 reference statements)
1
23
0
Order By: Relevance
“…16 Meanwhile, in December 2019, the pilot trial on cognitive-behavioural therapy for the management of IBD-fatigue by Artom et al has also been published. 17 The same evaluation was done for pharmaceuticaldriven studies in the past 3 years. In total, 63 studies were found using the ClinicalTrials.…”
Section: Resultsmentioning
confidence: 99%
“…16 Meanwhile, in December 2019, the pilot trial on cognitive-behavioural therapy for the management of IBD-fatigue by Artom et al has also been published. 17 The same evaluation was done for pharmaceuticaldriven studies in the past 3 years. In total, 63 studies were found using the ClinicalTrials.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this knowledge and their willingness to reduce the burden on respondents, they decided to proceed and modify the time commitment requirement. 36 We found only a few examples of recruitment feasibility studies in health disparities or diverse populations. Thus, most of our examples are from studies of less diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have focused on psychological factors, beliefs, and stress as causes and potential triggers [9,10]. Others have been curious about the e cacy of psychotherapeutic interventions for health amelioration, improved disease management, and even healing [11][12][13]. The outcomes of the research on the psychological issues prompted by this condition has not achieved unanimous agreement.…”
Section: Introductionmentioning
confidence: 99%